sEMG features extraction for back muscle impairment - Zainoddin, Muhamad Hafiy Syazwan; Chong, Shin Horng; Yahya, Abu Bakar (2014)
This paper discussed about the features extraction comparison between Low Back Pain (LBP) and Normal subjects. The objective of this research is to extract the features of SEMG signal in time and frequency domain. A group of 10 healthy subjects and 5 LBP subjects was chosen to determine the muscle condition during dynamic contraction activity which were sitting to stand and stand to sit activities. Each subject will complete the task 10 times respectively. Only multifidus muscle involved in this research. SEMG used to detect the signal from the muscle before being extracted by using time and frequency domain methods. Data collection will be classified by using neural network into 2 groups, normal and LBP.